Relationship of corporate governance on directors' remuneration of listed small and medium-scale companies in Malaysia - Mohamed Sultan, Siti Azura; Zainol, Zaini; Annuar, Hairul Azlan (Human Resource Management Academic Research Society, 2024)
Small and medium businesses play a significant role in the domestic economy. These businesses provide employment opportunities at lower and higher management levels with different employee remuneration schemes including directors. This research investigates the correlation between corporate governance characteristics and directors' remuneration within a sample of 50 small and medium-sized companies (SMCs) listed on Bursa Malaysia spanning the period 2015 to 2018. The GMM estimator results reveal a positive association between board size, board shareholding, family relationships, independent non-executive directors, and directors' remuneration. Conversely, a negative relationship is observed between the number of board meetings and directors' remuneration. The study suggests that regulators take these findings into account to mitigate agency problems within small and medium-sized listed companies in the country